2013
DOI: 10.1242/dev.084590
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of RNA-Seq data reveals involvement of JAK/STAT signalling during leg regeneration in the cricket Gryllus bimaculatus

Abstract: In the cricket Gryllus bimaculatus, missing distal parts of the amputated leg are regenerated from the blastema, a population of dedifferentiated proliferating cells that forms at the distal tip of the leg stump. To identify molecules involved in blastema formation, comparative transcriptome analysis was performed between regenerating and normal unamputated legs. Components of JAK/STAT signalling were upregulated more than twofold in regenerating legs. To verify their involvement, Gryllus homologues of the int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 58 publications
(56 citation statements)
references
References 33 publications
(45 reference statements)
2
54
0
Order By: Relevance
“…During the dedifferentiation and redifferentiation processes, the expression profiles of differentiated cell-related and stem cell-related genes change epigenetically (Barrero and Izpisua Belmonte, 2011;Katsuyama and Paro, 2011;Tamura et al, 2010). Our previous study showed that the expression levels of the epigenetic modifiers Gb'E(z) and Gb'Utx are upregulated during cricket leg regeneration (Bando et al, 2013). In this study, we examined the roles of these factors in leg regeneration.…”
Section: Discussionmentioning
confidence: 93%
See 4 more Smart Citations
“…During the dedifferentiation and redifferentiation processes, the expression profiles of differentiated cell-related and stem cell-related genes change epigenetically (Barrero and Izpisua Belmonte, 2011;Katsuyama and Paro, 2011;Tamura et al, 2010). Our previous study showed that the expression levels of the epigenetic modifiers Gb'E(z) and Gb'Utx are upregulated during cricket leg regeneration (Bando et al, 2013). In this study, we examined the roles of these factors in leg regeneration.…”
Section: Discussionmentioning
confidence: 93%
“…We previously showed that Gb'E(z) and Gb'Utx expression is upregulated within 24 h after cricket leg amputation (Bando et al, 2013), suggesting that Gb'E(z) and Gb'Utx might be involved early in the regeneration process, such as during the dedifferentiation into blastema cells. During Drosophila imaginal disc regeneration, the expression of Polycomb group genes, including E(z), is directly downregulated by JNK signalling in the wounding edge, increasing the plasticity of differentiated cells for promoting blastema formation (Lee et al, 2005).…”
Section: Epigenetic Regulation By Histone H3k27me3 Does Not Play a Romentioning
confidence: 99%
See 3 more Smart Citations